Website Profile Utilization Of Kube Serumpun As a Promotional Media - Rahmat Arif Ma’ruf; Gunawan Gunawan; Andi Lala; Sri Handayani (Jurnal Komputer, Informasi dan Teknologi, 2023)
Kube Serumpun is a trading business located in Tangsi Baru and sells snack products produced by Mrs. Mariamah's household. Kube Serumpun still carries out marketing strategies with an offline system in selling and promoting its products so that consumers lack information about more or less what products are offered. Kube Serumpun currently still does not have promotional media that uses technology, this results in Kube Serumpun becoming less known by the target market. In answering these problems, this study aims to create and utilize information technology based on company profile websites that can help Kube Serumpun and Consumers in delivering information effectively and efficiently. Systems developed using system prototyping and modeling are designed using UML which includes Use Cases, Activities, sequences, and classes. At the stage of system programming, programming is carried out using visual studio code, HTML, CSS, and JAVASCRIPT. The result of this research is information technology based on company profile websites that can introduce the identity of trading businesses and make it easier for consumers to obtain the information they want and become an effective marketing strategy in attracting consumers. And based on the results of Beta testing which was randomly distributed via google form with 18 respondents, the overall value of beta testing on Kube Serumpun profile websites got a value of 86.4%.